Susceptibility of Tribolium castaneum (Coleoptera: Tenebrionidae) and Trogoderma inclusum (Coleoptera: Dermestidae) to cold temperatures. (October 2015) - Arthur, F.H.; Hartzer, K.L.; Throne, J.E.; Flinn, P.W.
Abstract: Studies were conducted by exposing different life stages of Tribolium castaneum (Herbst), the red flour beetle, and Trogoderma inclusum (LeConte), the larger cabinet beetle, for different time intervals to −18 °C. Assessments were made of direct mortality to eggs, larvae, and adults, and eventual adult emergence of immatures. Data were described by non-linear equations. The eggs and larvae were the most tolerant life stage of T . castaneum . Eight hours of exposure were required for 100% kill of 3–4-day-old eggs and 0–10- and 11–21-day-old larvae, but only 4, 0.5, and 0.5 h respectively were required to completely inhibit adult emergence. For T . inclusum, the most tolerant life stage was 15–28-day-old larvae; 64 and 16 h respectively were required for complete mortality and inhibition of adult emergence. Results indicate that T . inclusum was the more tolerant species, and specific treatment protocols may be required for different stored product beetle species when using −18 °C as a disinfestation strategy. Highlights: Life stages and species of stored product insects vary in their response to cold temperatures. Trogoderma inclusum is more tolerant to cold temperature than Tribolium castaneum . Larvae of Trogoderma inclusum were the most tolerant life stage to cold temperature.